2020
DOI: 10.1002/chem.202001749
|View full text |Cite
|
Sign up to set email alerts
|

A Dimeric Chromium(II) Pincer as an Electron Shuttle for N=N Bond Scission

Abstract: Reduction of the bis-pyrazolyl pyridine complex [CrL] 2 with 4KC 8 ,f ollowed by addition of one azobenzene (overall mole ratio 1:4:1), PhNNPh, transfers reducing equivalents to three azobenzenes, to form [K 3 Cr(PhNNPh) 3 ]. This has three k 2 PhNNPh 2À ligands and K + bound to nitrogen atoms of azobenzene. When the stoichiometry is modified to 1:4:3, the product is changed to [K 2 CrL(PhNNPh) 2 ], which has C 2 symmetry except for the intimate ion pairingo ft wo K + ions to reduceda zobenzene nitrogen atoms,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…Only the benzo[c]cinnoline derivative undergoes N-N bond cleavage upon treatment with an excess of the reductant. Caulton's group demonstrated that the reaction of dichromium(II) complex 35 (vide supra) [57] with azobenzene yields the paramagnetic chromium(III) complex 77 having an unsymmetrically bridged PhNNPh unit (Scheme 23) [76]. The N-N distance of 1.471( 9 chloride counteranion.…”
Section: Redox Reactions Of Hydrazines and Azobenzenementioning
confidence: 99%
See 1 more Smart Citation
“…Only the benzo[c]cinnoline derivative undergoes N-N bond cleavage upon treatment with an excess of the reductant. Caulton's group demonstrated that the reaction of dichromium(II) complex 35 (vide supra) [57] with azobenzene yields the paramagnetic chromium(III) complex 77 having an unsymmetrically bridged PhNNPh unit (Scheme 23) [76]. The N-N distance of 1.471( 9 chloride counteranion.…”
Section: Redox Reactions Of Hydrazines and Azobenzenementioning
confidence: 99%
“…An analogous complex of a tetradentate ligand having non-protic pyridylmethyl arms displays no catalytic activity, even in the presence of external protic pyrazole as a proton source, indicating that the proton-responsive unit in the second coordination sphere is responsible for the N-N bond cleavage. Caulton s group demonstrated that the reaction of dichromium(II) complex 35 (vide supra) [57] with azobenzene yields the paramagnetic chromium(III) complex 77 having an unsymmetrically bridged PhNNPh unit (Scheme 23) [76]. The N-N distance of 1.471( 9 Electron transfer from the dichloromium(II) complex 35 to phenylhydrazine gives rise to the formation of the phenylhydrazido(2−)-bridged di(aniline)dichromium(III) complex 78 (Scheme 23) [77].…”
Section: Redox Reactions Of Hydrazines and Azobenzenementioning
confidence: 99%
“…This is a distinct difference from reaction of [CrL]2 with azobenzene, which reduces this by two electrons, in a sawhorse structure [Cr2L2(azobenzene 2-)] and then subsequent reduction by KC8 delivers electrons first to each of the two Cr, and only then are the electrons delivered to hydrazide, to give complete scission of the NN bond. [3] The established that [CrL]2 is not reducing enough to effect the twoelectron reduction of one benzoquinone to catecholate. We were interested in whether pre-reduction of [CrL]2 could further reduce the quinone.…”
Section: Attempted Four-electron Reduction Of [Crl]2mentioning
confidence: 99%
“…In addition to the electrophile-responsiveness at the βN of the pincer, the 1,4-diazabutadiene moiety is envisioned to temporarily store electrons and thereby aid the metal in the reduction of substrate. [2] In a previous report, we leveraged the Cr II /Cr III redox couple for single-or two-electron transfer from [CrL]2 for N=N bond reduction [3] and reductively promoted phenylhydrazine disproportionation. [4] Prompted by the rich cyclic voltammogram of [CrL]2 (see SI) we sought to explore here the outer sphere oxidation and reduction of [CrL]2, and progressive electron transfer to 3,5-di-tertbutyl benzoquinone.…”
Section: Introductionmentioning
confidence: 99%